A BRIEF REVIEW ON CRYOGUN MACHINE FOR PRE-CERVICAL CANCER HEALING - Aji Bagaskara; Rita Sundari; Rini Anggraini (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2021)
Cervical cancer is generally found in women of all ages due to  virus infection on epithelial cells of female cervix. It is known that a certain type of Human Papilloma Virus (HPV) is suspected to cause cervix cancer in women from various ethnics.   Several therapies have been used to cure cancer diseases like cone biopsy, laser treatment, electrosurgical excision, thermocoagulation, ablation therapy, and cryotherapy. This paper has highlighted on the role of cryogun machine applied in cryotherapy for pre-cervical cancer treatment in relation to freezing technique using liquid nitrogen to kill cancer cells on infectious area.